Insight into protist diversity in Arctic sea ice and melt-pond aggregate obtained by pyrosequencing - Estelle Silvia Kilias; Ilka Peeken; Katja Metfies (Polar Research, 2014)
Protists in the central Arctic Ocean are adapted to the harsh environmental conditions of its various habitats. During the Polarstern cruise ARK-XXVI/3 in 2011, at one sea-ice station, large aggregates accumulated at the bottom of the melt ponds. In this study, the protist assemblages of the bottom layer of the sea-ice and melt-pond aggregate were investigated using flow cytometry and 454-pyrosequencing. The objective is to provide a first molecular overview of protist biodiversity in these habitats and to consider the overlaps and/or differences in the community compositions. Results of flow cytometry pointed to a cell size distribution that was dominated by 3–10 µm nanoflagellates. The phylogenetic classification of all sequences was conducted at a high taxonomic level, while a selection of abundant (≥1% of total reads) sequences was further classified at a lower level. At a high taxonomic level, both habitats showed very similar community structures, dominated by chrysophytes and chlorophytes. At a lower taxonomic level, dissimilarities in the diversity of both groups were encountered in the abundant biosphere. While sea-ice chlorophytes and chrysophytes were dominated by Chlamydomonas/Chloromonas spp. and Ochromonas spp., the melt-pond aggregate was dominated by Carteria sp., Ochromonas spp. and Dinobryon faculiferum. We suppose that the similarities in richness and community structure are a consequence of melt-pond freshwater seeping through porous sea ice in late summer. Differences in the abundant biosphere nevertheless indicate that environmental conditions in both habitats vary enough to select for different dominant species.